Age and metabolic syndrome are associated with unsatisfactory improvement in nocturia after holmium laser enucleation of the prostate - Lv, Kaikai; Wu, Yangyang; Huang, Shuai; Luo, Zhenjun; Lai, Wenhui; Meng, Qingyang; Xia, Xinze; Lv, Chao; Hao, Xiaowei; Song, Tao; Yuan, Qing (Frontiers in Surgery, 2023)
Objective: To investigate the association between age, metabolic syndrome (MetS) and improvement in nocturia in patients with benign prostate hyperplasia (BPH) receiving holmium laser enucleation of the prostate (HoLEP). Methods: The retrospective study was conducted on patients treated for BPH using HoLEP between January 2021 and May 2022. Lower urinary tract symptoms (LUTS) were measured before surgery and at 3 months postoperatively using the International Prostate Symptom Score (IPSS). The criteria of the Adult Treatment Panel III (ATP III) were adopted to diagnose the MetS. Unsatisfactory improvement in nocturia was defined as < 50% reduction in nocturia from baseline on the IPSS. Results: One hundred and seventy-five patients were eventually enrolled, with a median age of 69 years (IQR: 63/73). Unsatisfactory improvement in nocturia was reported in 95 patients (54%) after HoLEP. These patients were older (73; IQR: 67/79 vs. 66; IQR: 60/71, P < 0.001) and more likely to present with higher postoperative total (6; IQR: 4/9 vs. 3; IQR:2/5, P < 0.001), voiding (1; IQR: 0/3 vs 1; IQR: 0/2, P = 0.017), and storage (4; IQR: 3/6 vs. 2; IQR: 1/4, P < 0.001) IPSS when compared to patients with satisfactory improvement in nocturia. Overall, 63 of 175 (36%) patients were diagnosed with MetS and of these, 44 (70%) reported unsatisfactory improvement in nocturia (P = 0.002) after HoLEP. Multivariate analysis revealed that age (OR = 1.117, 95% CI: 1.068– 1.169, P < 0.001) and MetS (OR = 3.613, 95% CI: 1.727– 7.562, P = 0.001) were independent risk factors for unsatisfactory improvement in nocturia after HoLEP. Conclusion: Our findings suggest that increased older and MetS were associated with unsatisfactory improvement in nocturia in patients with BPH after HoLEP. Lifestyle management, including weight loss, may be of great importance in the improvement in nocturia.